Analysis of the Rotor Magnetomotive Force of Built-In Radial Permanent Magnet Generator for Vehicle. (8th November 2021) - Geng, Huihui; Zhang, Xueyi; Si, Tao; Tong, Lanian; Ma, Qingzhi; Xu, Mingjun
Abstract : Permanent magnet generator (PMG) for vehicles has attracted more and more attention because of its high efficiency, high power density, and high reliability. However, the weak main air-gap magnetic field can affect the output performance and the normal use of electrical equipment. Aiming at the problem, this paper took the rotor magnetomotive force (MMF), the direct influencing parameter of the main air-gap magnetic field, as the research object, deduced the analytical expression of rotor MMF of the built-in radial PMG in detail, and analyzed its main influencing factors in analytical expression, including the permanent magnet steel (PMS) material, the thickness of PMS in magnetizing direction, the vertical length of the inner side of PMS, and the effective calculation length of PMS. Based on this, the rotor parameters were optimized to obtain the best values. After that, the finite element simulation and prototype test of the optimized generator were carried out. The comparative analysis results showed that the optimized rotor parameters could effectively improve the rotor MMF and optimize the output performance of the generator.